2012
DOI: 10.1519/jsc.0b013e31822a5cfe
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiac Autonomic Effects of High-Intensity Resistance Training Protocol in Wistar Rats

Abstract: The aim of this study was to assess the effects of metabolic and autonomic nervous control on high-intensity resistance training (HRT) as determined by pancreatic glucose sensitivity (GS), insulin sensitivity (IS), blood lactate ([La]), and heart rate variability (HRV) in rats. Thirty male, albino Wistar rats (292 ± 20 g) were divided into 3 groups: sedentary control (SC), low-resistance training (LRT), and HRT. The animals in the HRT group were submitted to a high-resistance protocol with a progressively incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…Corroborating, Deus et al. (2012) demonstrated that the LRT, without any additional load, is already sufficient to increase the load‐carrying capacity by the rodent, having its function enhanced by increasing the training load. In addition, morphological adjustments to peripheral nerves may explain, in part, the increase in muscle strength without necessarily increasing the size of the muscle or its fibers (Carbone et al., 2017).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Corroborating, Deus et al. (2012) demonstrated that the LRT, without any additional load, is already sufficient to increase the load‐carrying capacity by the rodent, having its function enhanced by increasing the training load. In addition, morphological adjustments to peripheral nerves may explain, in part, the increase in muscle strength without necessarily increasing the size of the muscle or its fibers (Carbone et al., 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Rodent sample number per group varied from 4 to 18 rats. Twenty‐three articles described the rat's initial body mass (Antonio‐Santos et al., 2016; Cassilhas et al., 2013; Deus et al., 2012; Deschenes et al., 1994; Deschenes, Sherman, Roby, Glass, & Harris, 2015; Domingos et al., 2012; Gil & Kim, 2015; Grans et al., 2014; Hornberger & Farrar, 2004; Jung et al., 2015; Krause Neto & Gama, 2017; Lee, Hong, & Kim, 2016; Mônico‐Neto et al, 2015; Nascimento et al., 2013; Neves et al, 2019; Padilha et al, 2017; Padilha et al., 2019; Prestes et al, 2009, 2012; Ribeiro et al, 2017; Shamsi et al, 2013; Souza et al., 2014; Tibana et al, 2017). Ladder‐based equipment structure varied from 1–1.3 m of height and 70–90° of inclination between studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training elicits numerous health‐related benefits . Resistance exercise has been shown to improve lipid profile , glucose tolerance and insulin sensitivity, increase basal metabolic rate, heart rate variability (HRV) and muscle and bone mass , and reduces body fat, blood pressure, and fatigue. In addition, phototherapy has been combined with dynamic exercise to enhance physical performance and improve health in experimental models and clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…Considerando que a mortalidade no DM está fortemente associada a complicações macro vasculares (aterosclerose), enquanto a disfunção microvascular (retinopatia, neuropatia e nefropatia) contribui significativamente para a Introdução 14 morbidade, o treinamento físico combinado pode ser uma importante estratégia no manejo da disfunção endotelial, a qual é um componente integral na patogênese da doença cardiovascular (Maiorana et al, 2001). De fato, o treinamento aeróbio realizado concomitantemente ao treinamento resistido de moderada-baixa intensidade pode ajudar a prevenir os efeitos de "endurecimento" vascular (stiffening) causados pelo treinamento resistido em remadores (Cook et al, 2006 (Barauna et al, 2005; ou mesmo em ratas ooforectomizadas Prestes et al, 2012;De Deus et al, 2012) foi administrada (Benzetacil, 40 000 U/Kg) (Latour et al, 2001;Irigoyen et al, 2005;. Os animais foram avaliados 9 semanas após a ooforectomia em função de trabalhos prévios de nosso grupo terem demonstrado que este tempo induz alterações que podem ser atenuadas pelo treinamento físico aeróbico dinâmico em ratas normais e diabéticas (Irigoyen et al, 2005; (Figura 2).…”
Section: Introdução 12unclassified